THE IMPORTANCE OF DIVERSIFICATION OF LAND USE IN THE DEVELOPMENT OF THE DISTRICT - Mahsudov Muhammadbek Dilshodbek ugli (Scholar Express Journals, 2021)
This article deals with the importance of land resources for sustainable economic development, the analysis of the experience of developed countries, and the diversification of the land fund. The author also provides theoretical suggestions and considerations.
Keywords: Land; land fund; types of land; exports